Public Awareness Regarding Household Drug Storage, Qassim Region, Saudi Arabia: A Cross-Sectional Study - Elghazaly A; Ben Salah G; Ibrahim N; Alsahali S; Widyan A; Altheyab G; AlKhelaiwi H; Al Mohammdi S (Dove Medical Press, 2023)
Abir Elghazaly,1 Ghada Ben Salah,2 Nada Ibrahim,1 Saud Alsahali,1 Adel Widyan,3 Ghaida Altheyab,4 Heba AlKhelaiwi,4 Sara Al Mohammdi4 1Department of Pharmacy Practice, Unaizah College of Pharmacy, Qassim University, Qassim, Saudi Arabia; 2Department of Pharmacology and Toxicology, Unaizah College of Pharmacy, Qassim University, Qassim, Saudi Arabia; 3Department of Mathematics, College of Science, Qassim University, Qassim, Saudi Arabia; 4Unaizah College of Pharmacy, Qassim University, Qassim, Saudi ArabiaCorrespondence: Saud Alsahali, Tel +966-163-011-503, Email s.alsahali@qu.edu.saBackground: Little is known regarding the post-dispensing storage conditions for pharmaceuticals in Saudi Arabia (SA). Most parts of the region are usually hot and humid, which could result in the decline of crucial performance parameters.Objective: To determine the prevalence of household drug storage habits in the population of Qassim, and to investigate their storage behaviors as well as knowledge and awareness of factors that may affect drug stability.Methods: A cross-sectional study was conducted using a simple random sampling technique in the Qassim region. Data were collected over a period of 3 months using a well-structured self-administered questionnaire and analyzed using SPSS version 23.Results: More than six hundred households from all regions of Qassim in SA participated in this study. Approximately 95% of the participants stored 1- 5 drugs at home. Analgesics and antipyretics were the highest household reported drugs (71.9%), with tablets and capsules dosage forms (72.3%). More than half of the participants (54.6%) stored drugs in their home refrigerators. Approximately 45% of the participants regularly checked the expiry dates of household drugs and immediately discarded them once their color changed. Only 11% of the participants shared drugs with others. We found that the number of drugs stored at home is heavily influenced by the number of family members in general and the number of members with medical issues in particular. Moreover, Saudi female participants with higher levels of education demonstrated better behaviors in terms of ensuring appropriate conditions for household drug storage.Conclusion: The majority of participants stored drugs in the home refrigerator or other easily accessible places, which may lead to toxicity or health risks, particularly for children. Therefore, population education and awareness programs should be implemented to raise awareness about the consequences of drug storage conditions in terms of the stability, efficacy, and safety of medications.Keywords: public awareness, household drugs, drug storage, Qassim